COMPREHENSIVE REVIEW OF CHRONIC LIMB-THREATENING ISCHEMIA: FROM PATHOPHYSIOLOGY TO INNOVATIVE TREATMENT APPROACHES - Bartosz Burda; Justyna Tasior; Michał Szalach; Rafał Gołacki; Paweł Szymonek; Mateusz Jasiński; Radosław Januszczak; Julianna Cholewa (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Chronic Limb-Threatening Ischemia (CLTI) represents the most advanced stage of peripheral artery disease (PAD) and is associated with a high risk of major amputation and mortality. Characterized by rest pain, non-healing ulcers, or gangrene, CLTI reflects severe systemic atherosclerosis with widespread cardiovascular involvement. The disease burden is increasing globally, particularly in aging populations with diabetes or hypertension.Methods: A literature review of PubMed, Scopus, and Google Scholar summarized current evidence on the definition, pathophysiology, classification, diagnostic strategies, and management of CLTI. It also highlights emerging research directions, including novel endovascular and surgical revascularization techniques, biologic and cell-based therapies, and evolving approaches to patient-centered care.Results: Advances in imaging modalities and revascularization strategies particularly endovascular, surgical, and hybrid techniques  have significantly improved limb salvage and survival rates. Recent studies emphasize the importance of individualized therapy and multidisciplinary management. Concurrently, innovative therapies focusing on angiogenesis, gene therapy, and regenerative medicine show promise for “no-option” patients, although further randomized trials are needed to validate long-term efficacy and safety.Conclusions: CLTI remains a complex and life-threatening condition requiring early diagnosis, comprehensive risk factor control, and personalized treatment planning. The integration of precision medicine, advanced imaging, and regenerative approaches holds the potential to redefine therapeutic strategies and improve patient outcomes. Future research should focus on optimizing patient selection, expanding access to limb-salvage interventions, and reducing global disease burden through preventive care.